Study on clinical waste management at healthcare centres in Kuantan, Pahang - Hilmi Wawardi, Haris (2019)
As any other developing countries, there are a significant increase in the generation of clinical waste over the last few decades. Even though clinical waste produce serious impact to the human and the environment, only minor attention is directed to its proper handling and legal aspects. This study seeks to examine the management of clinical waste in healthcare centre at Kuantan, Pahang. There are 10 healthcare centres that are involved in this study, and 10 respondents are surveyed from each healthcare centre. The research is conducted by using three methods, that are site visit, interview, and questionnaire. From the site visit and interview, we able to get the general information on the waste management of the hospital. From the questionnaire, we obtained the data on the demographic data of the respondent, and the data on clinical waste generation and management. Then, the data are analyse to produce the result. From the data that were analysed. Most of the type of clinical waste generated from the healthcare centres, are pharmaceutical waste, chemical waste, and sharps. The sources of these waste mainly from the patient and drugs. The method of segregation mainly used at the surveyed healthcare centres are by using machines. Most of the healthcare have the clinical waste collected once a week. Transportations of clinical waste by using trolley are mostly used at the surveyed healthcare centre. Most of healthcare centre that were surveyed has no incinerator. The handling of infectious waste is excellent at the healthcare centre. The clinical waste is segregated efficiently. The protective equipment is provided regularly by the healthcare centres and used properly. The respondents are satisfied with the handling of clinical. The clinical waste management training is effective and helps the respondents to improve the respondent knowledge on clinical waste management. Overall the effectiveness of the clinical waste management at the healthcare centres are excellent according to the respondents.